The Use of Short Stories with Hidden Pictures to Improve Students’ Vocabulary Achievement at Seventh Grade - Enung, Yoseph Nero Jack; Dania, Rahma (Journal of Research and Investigation in Education, 2024)
Short Stories (Cerpen) are literary works containing fictional stories packaged in a concise and clear form. The story presented is in the form of the author's imagination. Short stories have hidden images that can be used as learning media. Each noun in the story is replaced with a note that hides the picture of that noun. This research used subjects in seventh grade (VII) junior high school (SMP) level. The research stages were carried out in cycles of planning, action, observation and reflection. In the cycle stage there were four meetings with 13 class VII students at State Junior High School (SMPN) 5 Padang. This research was conducted on students who have limited vocabulary. Researchers recommend that an English teacher use short stories with hidden pictures as an alternative medium for learning vocabulary. The results of the paired sample test analysis show a p-value of 0.003 < 0.05 and a t-value of 3.792 with df -9. Thus, the Null Hypothesis (Ho) is rejected and the Alternative Hypothesis (Ha) is accepted and there is a significant increase in the use of short stories with hidden pictures to increase students' vocabulary achievement. So, this research can be a recommendation in using learning media to increase students' ability to master the components or other English skills in different classes, subjects and activities.